Soil factors are the drivers for wetlands colonization by Pneumatopteris afra in Nigeria - Festus, Akomolafe Gbenga; Rahmad Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2021)
The relationships between soil factors and plant community characteristics of some wetlands invaded by Pneumatopteris afra and non-invaded ones were investigated. Sixty soil samples were obtained from six wetlands comprising three invaded and three non-invaded in Lafia, Nigeria using sixty quadrants arranged on six 200 m transects. The samples, after air-dried and sieved using 2 mm mesh were analysed for the physico-chemical properties which include pH, organic matter (OM), percentage nitrogen (% N), phosphorus (P), calcium (Ca), sodium (Na), potassium (K), magnesium (Mg), exchangeable acidity (EA), percentage base saturation (% BS), particle size, porosity, bulk density (BD), hydraulic conductivity (HC), and moisture content (MC) using standard methods. Direct ordination in canonical correspondence analysis was used to determine the influence of these soil factors on P. afra abundance, Shannon diversity, and species richness of both invaded and non-invaded sites. All sites differ from each other in terms of their physico-chemical parameters. The invaded sites appeared to be more acidic (pH = 3.22), less sandy, more porous (38.11%), low HC (1.23) as compared with non-invaded ones. Soil factors that favoured abundance of P. afra (% OM and EA) correlated negatively with Shannon diversity index of invaded sites which was positively influenced by % N, pH, and cation exchange capacity (CEC). At the non-invaded sites, Shannon index and density were influenced positively by % BS, pH, AP, and % N. All these observations showed that the soil factors played significant roles in the establishment of P. afra at the invaded sites, and also on the plant diversity at non-invaded sites.